2022
DOI: 10.1038/s41385-022-00567-y
|View full text |Cite
|
Sign up to set email alerts
|

B-cell receptor physical properties affect relative IgG1 and IgE responses in mouse egg allergy

Abstract: Mutated and unmutated IgE and IgG play different and partly opposing roles in allergy development, but the mechanisms controlling their relative production are incompletely understood. Here, we analyzed the IgE-response in murine food allergy. Deep sequencing of the complementary-determining region (CDR) repertoires indicated that an ongoing unmutated extrafollicular IgE response coexists with a germinal center response, even after long-lasting allergen challenges. Despite overall IgG1-dominance, a significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 65 publications
2
13
0
Order By: Relevance
“…IgE, murine IgG1, and human IgG4 are produced by Th2-type cytokines, and IL-10 can induce a switch toward IgG4 and IgE inhibition, as shown in human studies (35). Elevated IgG4 levels have been associated with controlled allergic diseases in human studies (36). Although studies have found that class switch recombination to IgE occurs in the nasal tissues and bronchial mucosa (37,38), the class switch always occurs in mature B cells in the germinal centers of the spleen, nodes, and Peyer's patches (39).…”
Section: Discussionmentioning
confidence: 94%
“…IgE, murine IgG1, and human IgG4 are produced by Th2-type cytokines, and IL-10 can induce a switch toward IgG4 and IgE inhibition, as shown in human studies (35). Elevated IgG4 levels have been associated with controlled allergic diseases in human studies (36). Although studies have found that class switch recombination to IgE occurs in the nasal tissues and bronchial mucosa (37,38), the class switch always occurs in mature B cells in the germinal centers of the spleen, nodes, and Peyer's patches (39).…”
Section: Discussionmentioning
confidence: 94%
“…46 Sequential switching via IgG1 in mice was proposed 37 and has since been shown to be the main mechanism by which such IgE arises, 129 although, a recent study challenges this notion. 130 46 IgE responses also ensue via the extrafollicular route for long periods in parallel with GC responses, 131 and unmutated clones are found among IgE + B-lineage cells of atopic individuals. 39 Therefore, during type 2 immune responses such as allergies, IgE + ASC can arise via the extrafollicular route, but mainly form from the differentiation of GC or post-GC mBC populations; whether GC or post-GC mBC are the dominant source is unclear.…”
Section: Cellul Ar Source S Of I G E + a Scmentioning
confidence: 99%
“…Which is the dominant formation route of IgE ASC is a current question. It may be possible to visualize this with in vivo microscopy in dual fluorescent IgE and ASC reporter mouse strains, and literally see whether GC 137 or the recently defined subcapsular sinus proliferative foci 141 are the sites of IgE + ASC differentiation, but sequencing studies also provide insight into IgE + ASC relationships to precursors 39,131 …”
Section: Cellular Sources Of Ige+ Ascmentioning
confidence: 99%
See 2 more Smart Citations